Conceptual framework of rural landscape character assessment to guide tourism development in rural areas - Zakariya, Khalilah; Ibrahim, Putri Haryati; Abdul Wahab, Nur Amirah (Penerbit Universiti Sains Malaysia, 2019)
The landscape character of a rural area is the distinct patterns that are shaped by the natural, built and cultural elements found in a particular setting. The rural landscape character is an important component of the rural landscape corridor, particularly in shaping a scenic driving route. Due to urbanisation, the improvements of road infrastructure and conversion of agricultural lands into commercial land use, the rural landscape may gradually lose its unique characters if they are not integrated into the development planning strategies. There have been a growing number of researchers that examine the landscape character assessment framework and studies on the rural areas. However, a framework that is tailormade to examine the rural landscape is needed to assist landscape architects and planners to identify and map the landscape values prior to planning any development in the rural areas, as these values are also vital in attracting rural tourism. The aim of this article is to formulate a conceptual framework on landscape character assessment for the rural landscape corridor. The framework proposes the addition of intangible components that relate to the tangible components of the rural landscape character. The framework can guide the planning of rural areas and the rural corridor.